2007
DOI: 10.1093/rheumatology/kem171
|View full text |Cite
|
Sign up to set email alerts
|

Patient education in rheumatoid arthritis: the effectiveness of the ARC booklet and the mind map

Abstract: The ARC booklet with or without the mind map was associated with a significant increase in knowledge. Poor readers had poor educational attainment and poor knowledge acquisition. The information on the mind map was not more accessible to them. Different educational strategies will be necessary to educate these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 13 publications
3
53
1
9
Order By: Relevance
“…11 Walker and colleagues found health literacy to be significant and positively associated with health knowledge. 12 Lack of knowledge left patients unable to recognize and respond to adverse side effects as reported by Davis et al 13 US Department of Health and Human Services searched several databases. According to this survey, many studies measured the relationship between literacy levels and knowledge of the use of health care services: Mammography, Cervical cancer screening, Emergency department discharge instructions, Heart Health Knowledge and informed consent, all of these demonstrated a statistically significant association between higher literacy level and knowledge of matters relating to use of these health services.…”
Section: Discussionmentioning
confidence: 99%
“…11 Walker and colleagues found health literacy to be significant and positively associated with health knowledge. 12 Lack of knowledge left patients unable to recognize and respond to adverse side effects as reported by Davis et al 13 US Department of Health and Human Services searched several databases. According to this survey, many studies measured the relationship between literacy levels and knowledge of the use of health care services: Mammography, Cervical cancer screening, Emergency department discharge instructions, Heart Health Knowledge and informed consent, all of these demonstrated a statistically significant association between higher literacy level and knowledge of matters relating to use of these health services.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors claimed that the concept map was a good way to add to the patients' knowledge and foster empowerment. In contrast, Walker et al [23] found no difference in their randomized study of 363 patients. The education used either a booklet combined with a mind map-type visual aid, or the booklet alone.…”
Section: -Concept Mapping As a Learning Aid During Education Sessionsmentioning
confidence: 89%
“…The studies that were found had varying results with regard to the effects of using concept mapping on patients [21][22][23]. That variability was due, in part, to the fact that different effects were being measured; two studies looked at the effects on knowledge [22,23], and a third looked at the impact on quality of life [21].…”
Section: Little Exploration Of Cm's Effects On Patientsmentioning
confidence: 99%
See 2 more Smart Citations